Functional quality traits of snake melon (Cucumis melo var. flexuosus L.) fruits as affected by genotypic differences - Ilahy, Riadh; Tlili, Imen; Rouhou, Hela Chikh; R him, Thouraya; Homa, Fozia; Hdider, Chafik; Jebari, Hajer; Lenucci, Marcello Salvatore (Journal of Postharvest Technology, 2024)
This study reports the variability affecting the main antioxidant components and the antioxidant activities of three F1 hybrids (KP7, LP5 and XP12), six  breeding lines (L1P3, L2P4, L4P18, L5P10, L6P4, L9P1) of snake melon (Cucumis melo var. flexuosus L.) and the widely grown and consumed  cultivar Mornagui grown under greenhouse during the seasons 2014 and 2015. The functional quality varied significantly (P < 0.05) depending on the  cultivar. The F1 hybrid LP5 was the richest cultivar in total phenols (47.6 mg GAE/kg fw). The breeding line L4P18 was characterized by a peak of total  carotenoids (36.1 mg β-Ca. E/kg fw) and flavonoids (231.6 mg RE/kg fw), while L9P1 ranked first for ascorbic acid (AsA) (146.0 mg/kg fw),  dehydroascorbic acid (DHA) (231.2 mg/kg fw) and total vitamin C (377.2 mg/kg fw). The antioxidant activity of the hydrophilic and lipophilic fractions  were greater in XP12 and L2P4 (˃215 µM Trolox/100 g fw) and L1P3 (458.2 µM Trolox/100 g fw) than all other genotypes. These findings are useful  for 1) researchers targeting the development of snake melon cultivars with satisfying functional quality and 2) consumers searching for alternative  sources of natural antioxidants.
Keywords: Fakous,; functional quality; hydrophilic and lipophilic antioxidant activity; snake melon